Simulation of the machine loading decision in flexible manufacturing cell based on FlexSim environment - T.Nguyen, H.; N.Tran, Q.; P. Rifai, A.; N.Huynh, H.; Zawiah Md Dawal, Siti (International Journal of Engineering and Technology, 2018)
This paper presents a simulation study to understand the behavior of flexible manufacturing cell (FMC) based on the optimal machine loading decision obtained from analytical approach. The machine loading model considered the allocation of machine and operation of each part in its batch in manufacturing environment. The simulation experiment is utilized to evaluate the effects of the most suitable combination of machines and operations in FMC, in relation to the system unbalance, makespan and total flow time based on two experimental scenarios, with 4 machines and 5 part types/8 part types. Results highlighted the competitive performance of obtained optimal loading solution and confirmed the reasonableness of the designed cell. Moreover, the comparison of performance indicators also confirmed that the FlexSim is a helpful and powerful tool to validate the optimal solutions from analytical approach. Finally, the machine loading decision of FMC is effective to be applied in real system at the manufacturing small and medium enterprises (SMEs).Â